#### Answer

x = -2

#### Work Step by Step

1. Given: 6x - 3(5x + 2) = 4(1 - x)
2. Apply Distributive Property: 6x - 15x - 6 = 4 - 4x
3. Add and subtract: -5x = 10
4. Divide: x = -2
5. Check: 6(-2) - 3(5*-2 + 2) = 4(1 - (-2))
12 = 12 , so -2 is a solution.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

x = -2

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.